“This above all: to thine own self be true…” the effects of the COVID-19 pandemic on surgical residency training and education - Dockter, Andrew Grayson; Angelos, George C. (International Surgery Journal, 2020)
COVID-19 has drastically affected the current surgical training paradigm. Fellows anticipate a 10-25% decrease in procedural volumes for this year because of the pandemic. With a reduction in elective cases, surgical programs have transitioned to resident coverage cutbacks and/or reassigning trainees to non-surgical wards to assist with pandemic relief.